Foreign Exchange Risk in the Eurozone - Charalambous, Soteria (My University, 2025)
This dissertation studies the ramifications of foreign exchange risk for Eurozone-listed public corporations. Through the estimation of popular asset pricing models and the application of rigorous testing, it provides evidence on the significance of foreign exchange risk in the determination of stock returns for Eurozone corporations. Chapter 1 documents a negative and statistically significant relationship between a firm’s sensitivity to foreign exchange rate changes and its stock returns. This relationship persists even after controlling for various firm characteristics such as market beta, market capitalization, book-to-market ratio, momentum, and profitability. Chapter 1 also identifies two prominent asset pricing anomalies in the Eurozone: profitability and momentum but does not find evidence of size anomaly. Chapter 2 provides estimates of several well-known asset pricing factors that are Eurozone-specific. Subsequently, it extends the asset pricing models by introducing a foreign exchange sensitivity factor to evaluate whether foreign currency risk is systematic. It finds evidence of systematic pricing of foreign exchange risk in Eurozone stock returns. Chapter 3 focuses on Eurozone corporations’ foreign (outside the Eurozone) sales as incorporated in the foreign asset turnover ratio (foreign sales relative to total assets). It documents a positive and statistically significant relationship between this ratio and stock returns during periods of euro depreciation. The positive relationship holds even after controlling for various firm characteristics.
Keywords: foreign exchange risk; asset pricing anomalies; foreign sales; asset turnover; stock returns; Eurozone